(untitled) (Mongolian Journal of Humanities and Social Sciences, 2023)
This paper intends to give a clear picture of how I, as a reader, react to the social and political situations described in Arthur Miller’s The Crucible. The title of this paper obviously refers to the historical facts behind the play. To reach my target, I must permit myself to imagine the two different periods and their contexts, therefore, the exposition of facts may not be linear. The paper is organized into 2 main parts. In the first part, on the basis of the historical background of the two different periods in American History, I’d like to argue that the people’s superstitious beliefs in witchcraft are considered as the use and didactic principle of changing the whole society. The second part, on the basis of the social and political background of the Witch-hunts in 1692 and the Cold War, which led to McCarthyism, intends to draw that McCarthyism is considered as an influential event which can be seen as a response to the occurrence of witch trials to cure them. The consequences of these historical parallel events on the society will be discussed. It also compares the similar fates of both witches and Communists throughout time. Артур Миллерийн “Хэцүү сорилт” жүжигт нийгэм, улс төрийн байдлыг дүрсэлсэн нь Хураангуй: Энэхүү өгүүлэл нь Артур Миллерийн “Хэцүү сорилт” жүжигт дүрсэлсэн нийгэм, улс төрийн нөхцөл байдлыг тодорхойлон бичихийг зорилоо. Зохиолд Америкийн түүхийн хоёр өөр үеийг баримтат үйл явдлуудаар дүрсэлсэн харуулахыг оролдсон. Судалгаа нь хоёр хэсгээс бүрдсэн: эхний хэсэгт хүмүүсийн мухар сүсэгт итгэж буй итгэл үнэмшлээр дамжуулан нийгмийг хэрхэн өөрчилж буйг, хоёр дахь хэсэг нь 1692 оны нийгэмд өрнөж буй антикоммунист үзэлтэн буюу нийгэмд аюултай тэрсүүд үзэлтнүүдийг засан хүмүүжүүлэх, Маккартизмыг эсэргүүцэх үйл ажиллагаа, түүний нийгэмд учруулж буй үр дагаварт анализ хийж, тодорхойлон бичихийг оролдсон болно. Түлхүүр үг: улс төр, нийгмийн нөхцөл байдал, мухар сүсэг, итгэл үнэмшил, антикоммунист үзэл, Маккартизм